General fifth m-zagreb indices and fifth m-zagreb polynomials of crystal cubic carbon - Zahid M.A.; Naeem M.; Baig A.Q.; Ggao, Wei (Utilitas Mathematica, 2022)
Graph theory plays a vital role in modeling and designing any chemical structure or chemical network. Chemical graph theory helps in understanding about the molecular structural properties of a molecular graph. The molecular graph is a graph consists of atoms called vertices and the chemical bond between atoms called edges. In this paper, we have computed the general fifth Af- Zagreb indices and fifth A/3-Zagreb index and their polynomials of a molecular graph namely Crystal Cubic Carbon denoted by CCCn) for n-levels. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.